Effects of elevated CO2 on activities of protective and detoxifying enzymes in Frankliniella occidentalis and F. intonsa under spinetoram stress. Issue 1 (19th September 2021) - Fan, Zongfang; Qian, Lei; Chen, Yaping; Fan, Rui; He, Shuqi; Gao, Yulin; Gui, Furong
Abstract: BACKGROUND: Elevated CO2 can directly affect the toxicity of insecticides to insects and the physiological response of insects to insecticides. Frankliniella occidentalis and F. intonsa are highly destructive pests that target horticultural crops. Spinetoram is an effective pesticide against thrips. This study sought to explore the effect of elevated CO2 on efficacy of spinetoram against F. occidentalis and F. intonsa and effect of the spinetoram on activities of protective and detoxifying enzymes under elevated CO2 . Notably, these enzymes can be exploited in further studies to develop interventions for thrips resistance management. RESULTS: Toxicity bioassay showed that the LC50 values of F. occidentalis and F. intonsa exposed to spinetoram at elevated CO2 (800 μL L −1 concentration) for 48 h was 0.08 and 0.006 mg L −1, respectively, which is 0.62 and 0.75 times of the values at ambient CO2 (400 μL L −1 concentration). The findings showed that elevated CO2 decreased activities of the superoxide dismutase and acetylcholinesterase in thrips, while increasing the activities of carboxylesterase and glutathione S ‐transferase. However, spinetoram increased activities of protective and detoxifying enzymes in both thrips under the two CO2 levels. Elevated CO2 and spinetoram affect the physiological enzyme activity in thrips synergistically, and the activities of analyzed enzymes were generally higher in F. occidentalis than in F. intonsa . CONCLUSION: Elevated CO2 amplifies the efficacy of spinetoram on thrips, F. intonsa is more susceptibility to spinetoram than F. occidentalis and the latter showed better adaptation to adverse conditions than the former. © 2021 Society of Chemical Industry. Abstract : Elevated CO2 amplifies the efficacy of spinetoram on thrips. Frankliniella occidentalis showed higher resistance to spinetoram than F. intonsa .